Defiance - Cherryh, C. J.; Fancher, Jane, 1952- (Cherryh, C. J. Foreigner universe, 2023)
"In the east, outright warfare has tied down the Assassins' Guild, and that region is in confusion. Ready to hand is an age-old feud in the west, where the Master of Ashidama Bay has long hated the Edi people of the north shore and equally hated the Aishidi'tat for bringing the Edi to his shores--and hatred is a resource the Shadow Guild knows how to use to its advantage. Bren Cameron is tasked with getting Ilisidi, the aiji-dowager, back to the capital alive, on an urgent basis. But events are cascading down on the south, the Guild is stretched thin in the east, and the Shadow Guild is within striking distance of critical targets that could bring war to the entire south. Two lives stand in the breach, two lives the aishidi'tat would not willingly risk--Ilisidi and Bren--and the Shadow Guild will spend anything and everything to take them out" --